Methods in Quaternary Ecology #12. Vertebrates - Churcher, C.; Wilson, M. (Geoscience Canada, 1990)
Summary The original fascination of scholars with Quaternary vertebrates was more related to their sometimes astonishing size and characteristics than to their value in paleoenvironmental reconstruction. The dominant place occupied by Quaternary vertebrates in the paleontological literature owes much to the high visibility of larger species as well asto our own affinity with the Mammalia. Nevertheless, it is clear that vertebrate fossils have enormous potential in the reconstruction of ancient climates and environments. This po-tential extends to the detection of unusual environmental parameters, such as extentand severity of seasonal stresses and even such a specific factor as depth of winter snow. Although many of the larger Quaternary mammals became extinct, modern analogues exist for a large number of fossil forms, allowing inferences of temperature,moisture, substrate, vegetative cover or presence of particular food plant species. Further, the study of small vertebrates, whether mammals or other species, allows paleontologists to make similar inferences based on animals that are relatively tied to one place and cannot migrate as do large ungulates orbirds. Information obtained from these dis-parate sources can serve as a primary suiteof proxy environmental data, as a cross-check on other proxy sources, or as an element to be used in complex transfer functions employing input from multiple proxysources. As methods are refined, the potential for dating bones and teeth directly through radiocarbon, amino-acid racemization, electron spin resonance, uranium-series or other methods should ensure that vertebrate remains will also be of great value in establishing absolute time-sequences of local and regional environmental changes.